Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kepuasan Kerja Karyawan dengan Motivasi Kerja Sebagai Variabel Mediasi( Survei pada Karyawan PT. Indo Acidatama Tbk.) - Wahyuningsih; Fii Ahsani , Riska (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Work Env Human resources are an important aspect in achieving company success. One of the company's successes is marked by good employee job satisfaction. A comfortable work environment, well-distributed workload and high work motivation will contribute to employee job satisfaction. This research aims to analyze the significance of the influence of the work environment and workload on job satisfaction with work motivation as a mediating variable in PT employees. Indo Acidatama Tbk. The population of this research is employees of PT. Indo Acidatama Tbk located in Karanganyar. The type of data used is quantitative data. The data source used is primary data. The sampling technique used unproportional random sampling with a sample size of 80 respondents. Data collection was carried out by distributing questionnaires. The data analysis method in this research is multiple linear analysis and Sobel test using SPSS as a data processing tool. The results of this research are that the work environment and workload have a significant effect on the work motivation of PT Indo Acidatama Tbk employees, the work environment has no significant effect on the job satisfaction of PT Indo Acidatama Tbk employees, workload and work motivation have a significant effect on PT Indo Acidatama Tbk employees, work environment and workload have a significant effect on job satisfaction through the work motivation of PT Indo Acidatama Tbk employees. The R2 value for the work environment variable (X1) and workload (X2) for the dependent variable, namely work motivation (Y1) is 46.4%. Meanwhile, the remaining 53.6%, meaning that work motivation is explained by other variables, such as: work discipline, employee performance, length of service, level of education and so on which were not examined in this research. The R2 value of work environment independence (X1), workload (X2) and work motivation (Z) on job satisfaction (Y) is 35.5%. While the remaining 64.5%, meaning that job satisfaction is explained by other variables, such as: compensation, organizational structure, leadership style and promotion.